Traditional Knowledge as a Significant Factor in the Formation of Ethnic and Cultural Heritage of Ukraine's Population - Швидкий, С. М. (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The task of folk knowledge research is one of the main tasks in modern ethnology. This knowledge demonstrates features of national and simultaneously regional distinctiveness. The area of learning folk medicine is the most typical in this originality. It had been formed as a system for centuries and united into rational and irrational knowledge, mystical and practical experience, pagan and Christian view of the human’s being. Learning of folk medicine in ethnological dimension allows solving the important research tasks related with the problems of the nations’ development, its coexistence with other elements of sociocultural space.